Increase in Incidence Rates and Risk Factors for Multidrug Resistant Bacteria in Septic Children: A Nationwide Spanish Cohort Study (2013-2019) - María Slocker-Barrio; Jesús López-; Amaya Bustinza-Arriortúa; Elena Fresán-Ruiz; Iolanda Jordán-García; Juan Carlos de Carlos-Vicente; Elvira Morteruel-Arizcuren; Patricia García-Soler; Montserrat Nieto-Moro; Cristina Schüffelmann; Sylvia Belda-Hofheinz; Laura Ximena Herrera-Castillo; et al. (MDPI AG, 2023)
The emergence of multidrug-resistant (MDR) bacteria in children is a growing concern, particularly among septic patients, given the need for first-right dosing. Our aim was to determine the incidence rates and factors associated with MDR-sepsis in the pediatric intensive care unit (PICU), using data from the Spanish ENVIN-HELICS PICU registry between 2013 and 2019. The rate of MDR bacteria among septic children ranged between 5.8 and 16.2% throughout this study period, with a significant increase since 2015 (p = 0.013). MDR-gram-negative bacteria (92%), particularly EBL-Enterobacterales (63.7%), were the most frequent causative microorganisms of MDR-sepsis. During this study period, sixteen MDR-sepsis (32.6%) corresponded to intrahospital infections, and 33 (67.4%) had community-onset sepsis, accounting for 10.5% of the overall community-onset sepsis. Independent risk factors associated with MDR-sepsis were antibiotics 48 h prior to PICU admission (OR 2.38) and PICU onset of sepsis (OR 2.58) in >1 year-old children, and previous malnourishment (OR 4.99) in <1 year-old children. Conclusions: There was an alarming increase in MDR among septic children in Spain, mainly by gram-negative (ESBL-Enterobacterales), mostly coming from the community setting. Malnourished infants and children on antibiotics 48 h prior to PICU are at increased risk and therefore require closer surveillance.